DMF Attenuates Ciprofloxacin-Induced Nephropathy in Rats via Nrf2 Pathway (Journal of Pharmaceutical Negative Results, 2022)
Background: The pathophysiology of ciprofloxacin-induced nephropathy (CIN) is complicated by oxidative stress. The goal of this studywas to see if Dimethyl Fumarate (DMF) has any antioxidant properties in a rat model of CIN.Methods: Rats were randomly assigned to six groups (n=8): control, ciprofloxacin (ciprofloxacin-induced CIN), two DMF groups (ratstreated with DMF 50mg and 100mg), and two ciprofloxacin Plus DMF groups (n=8/group) (CIN rats treated with DMF at 50 mg and 100mg). Renal function testing, Nrf2 analysis, and anti-oxidant enzymes analysis was all done. Results: Following ciprofloxacin therapy, serumblood urea nitrogen (BUN), creatinine, and anti-oxidant enzymes all rose. In the ciprofloxacin + DMF groups, serum BUN and creatininewere lower, and anti-oxidant enzymes were higher than in the ciprofloxacin group, in CIN rats, DMF upregulated Nrf2 expression.Conclusions: In vivo, DMF reduces experimental CIN. It’s thought that this impact activates the Nrf2 antioxidant defenses pathway